2023
DOI: 10.3389/fneur.2023.994877
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo time course of organ uptake and blood-brain-barrier permeation of poly(L-lactide) and poly(perfluorodecyl acrylate) nanoparticles with different surface properties in unharmed and brain-traumatized rats

Abstract: BackgroundTraumatic brain injury (TBI) has a dramatic impact on mortality and quality of life and the development of effective treatment strategies is of great socio-economic relevance. A growing interest exists in using polymeric nanoparticles (NPs) as carriers across the blood-brain barrier (BBB) for potentially effective drugs in TBI. However, the effect of NP material and type of surfactant on their distribution within organs, the amount of the administrated dose that reaches the brain parenchyma in areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 114 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…As the primary cell type of BBB, EC survival is responsible for the BBB integrity. 20 It has been shown that TBI could induce EC apoptosis, thus destroying BBB. 21 To verify the occurrence of EC apoptosis, we firstly used double IF staining of TUNEL and CD31 (an EC marker).…”
Section: Resultsmentioning
confidence: 99%
“…As the primary cell type of BBB, EC survival is responsible for the BBB integrity. 20 It has been shown that TBI could induce EC apoptosis, thus destroying BBB. 21 To verify the occurrence of EC apoptosis, we firstly used double IF staining of TUNEL and CD31 (an EC marker).…”
Section: Resultsmentioning
confidence: 99%